35. Visual evoked potentials and MRI in monitoring optic nerve involvement in a relapsing remitting model of EAE. Issue 1 (January 2015) - Santangelo, R.; Castoldi, V.; Camaleonti, L.; Cursi, M.; Dina, G.; Comi, G.; Quattrini, A.; Chaabane, L.; Leocani, L.
<x xml:space="preserve">Abstract</x> Experimental Autoimmune Encephalomyelitis (EAE) is a pre-clinical disease model of Multiple Sclerosis (MS), traditionally induced by injecting Myelin Oligodendrocyte Glycoprotein(MOG). Optic nerve involvement and VEP diagnostic reliability have been already shown in MOG induced EAE rat. In the present study we used spinal cord homogenate (SCH) to induce disease in Dark-Agouti (DA) rats, proposing to show optic nerve involvement and assess VEP usefulness as neurophysiological biomarker also in this model. Nineteen DA rats were used in the experiment: 7 immunized by SCH (EAE) and 12 healthy (H) controls. Flash VEPs from both eyes were recorded with epidural electrodes under sevoflurane volatile anesthesia once a week for 6 weeks (one day before immunization, days 6, 13, 20, 27, 34 post) with measurement P1 latency from N1-P1-N2 complex. Values exceeding 2.5 SD from control mean were considered abnormal. MRI analyses on both Optic Nerves were also performed using a 7 Tesla technology. After the last VEP session, 7 EAE and 3 H animals underwent histological analysis on a transverse section of both optic nerves. P1 latency in EAE group was significantly increased at days 13–20-27 post immunization and was abnormal in 10/14 eyes in EAE rats (p < 0.05). Neither histology nor VEPs showed pathologic findings in any H control. MRI analysis showed Fractional Anistropy (FA) and Diffusion Tensor Imaging (DTI) pathological values in EAE rats, too. Histological optic nerve damage was found in 6/14 eyes in EAE, with a 57% agreement between VEPs and histologic data. Considering histology data as the gold standard, in our EAE model VEPs showed a sensitivity of 83% and a specificity of 37%. Our data show optic nerve involvement in SCH EAE in DA rats. VEPs latencies are significantly delayed in EAE and show a good sensitivity in identifying affected eyes such as MRI analysis. Suboptimal agreement between histology and VEPs and lowest VEP specificity are probably due to single optic nerve sections that may underestimate actual optic nerve involvement, because of patchy disease pattern. On the other hand, VEPs abnormalities may also derive from lesions affecting the visual pathways behind the optic chiasm. In any case, these findings suggest that VEPs could be a useful tool in monitoring the disease course in SCH-EAE and prompt further studies specifically addressing their value in testing novel treatments.